Diabetes and Heart Failure: Is it Hyperglycemia or Hyperinsulinemia? - Didangelos, Triantafyllos; Kantartzis, Konstantinos (Current Vascular Pharmacology, 2020)
The cardiac effects of exogenously administered insulin for the treatment of diabetes (DM) have recently attracted much attention. In particular, it has been questioned whether insulin is the appropriate treatment for patients with type 2 diabetes mellitus and heart failure. While several old and some new studies suggested that insulin treatment has beneficial effects on the heart, recent observational studies indicate associations of insulin treatment with an increased risk of developing or worsening of pre-existing heart failure and higher mortality rates. However, there is actually little evidence that the associations of insulin administration with any adverse outcomes are causal. On the other hand, insulin clearly causes weight gain and may also cause serious episodes of hypoglycemia. Moreover, excess of insulin (hyperinsulinemia), as often seen with the use of injected insulin, seems to predispose to inflammation, hypertension, dyslipidemia, atherosclerosis, heart failure, and arrhythmias. Nevertheless, it should be stressed that most of the data concerning the effects of insulin on cardiac function derive from in vitro studies with isolated animal hearts. Therefore, the relevance of the findings of such studies for humans should be considered with caution. In the present review, we summarize the existing data about the potential positive and negative effects of insulin on the heart and attempt to answer the question whether any adverse effects of insulin or the consequences of hyperglycemia are more important and may provide a better explanation of the close association of DM with heart failure.
Keywords: Diabetes